Effect of Varying Levels of Dietary Protein and Energy on Performance of Commercial Broiler Chicken - Bhagat, Vikas R.; Mishra, Ram Kailash; Patel, Atul B.; Rajpura, Rais M.; Bhagora, Nikesh J.; Savaliya, Fulabhai P (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
One hundred and sixty (160) straight run day-old commercial broiler chicks were randomly divided into 5 dietary treatments with four replicates having 8 chicks in each replicate. The five dietary treatments with varying levels of CP and ME were: T1 diet with 21, 20 and 18% CP and 2800, 2900 and 3000 Kcal/kg ME in pre-starter, starter and finisher mash, respectively. T2 diet with 22, 21 and 19% CP and 2900, 3000 and 3100 Kcal/kg ME in pre-starter, starter and finisher mash, respectively. T3 diet was kept as basal diet as per BIS (23, 22 and 20% CP and 3000, 3100 and 3200 Kcal/kg ME in pre-starter, starter and finisher mash, respectively). T4 diet with 24, 23 and 21% CP and 3100, 3200 and 3300 Kcal/kg ME in pre-starter, starter and finisher mash, respectively. T5 diet with 25, 24 and 22% CP and 3200, 3300 and 3400 Kcal/kg ME in pre-starter, starter and finisher mash, respectively. Body weight and body weight gain of birds were significantly (p <0.05) higher in group fed with T5 ration than the birds fed with T1, T2, T3 and T4 rations. Feed consumption was significantly (p <0.05) higher in group fed with T4 ration than the birds fed with other rations. Feed conversion ratio was improved significantly (p <0.05) in birds fed with T5 ration than the birds fed with T1, T2, T3 and T4 rations. However, T1 ration resulted in higher economic return (Rs./bird) in terms of return over feed cost (Rs. 47.61), followed by T5, T2, T3 and T4 diet (Rs. 36.28, 30.96, 21.04 and 20.59, respectively).